2023
DOI: 10.3389/fphar.2023.1091976
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding and intergenic genetic variants of human arylamine N-acetyltransferase 2 (NAT2) gene are associated with differential plasma lipid and cholesterol levels and cardiometabolic disorders

Abstract: Arylamine N-acetyltransferase 2 (NAT2) is a phase II metabolic enzyme, best known for metabolism of aromatic amines and hydrazines. Genetic variants occurring in the NAT2 coding region have been well-defined and are known to affect the enzyme activity or protein stability. Individuals can be categorized into rapid, intermediate, and slow acetylator phenotypes that significantly alter their ability to metabolize arylamines, including drugs (e.g., isoniazid) and carcinogens (e.g., 4-aminobiphenyl). However, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…This finding also supports the association of the haplotype with differential systemic NAT2 activity (i.e. acetylator phenotype) [7]. This suggests that the differential risks of dyslipidemia and urinary bladder cancer are associated with and influenced by the NAT2 acetylator phenotype (Table 1).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…This finding also supports the association of the haplotype with differential systemic NAT2 activity (i.e. acetylator phenotype) [7]. This suggests that the differential risks of dyslipidemia and urinary bladder cancer are associated with and influenced by the NAT2 acetylator phenotype (Table 1).…”
supporting
confidence: 77%
“…For instance, rs35246381-C, which is in linkage disequilibrium with rs1495741-G, is associated with elevated serum levels of caffeine metabolites (e.g. 5-acetylamino-6-amino-3-methyluracil and 5-acetylamino-6-formylamino-3-methyluracil), which can be attributed to relatively high NAT2 activity [7]. This finding also supports the association of the haplotype with differential systemic NAT2 activity (i.e.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…N-acetylputrescine was associated with higher levels of triglycerides and HDL-C. Similarly, Hong et al found that SNP rs35570672-T, which is associated with hyperlipidemia, was also associated with elevated levels of N-acetylputrescine [ 57 ]. Increased levels of N-acetylputrescine have been associated with disease severity in patients with liver and kidney disease [ 58 ].…”
Section: Discussionmentioning
confidence: 99%